Effect of integrated approach of plant nutrients on yield and yield attributes of different crops in wheat-sesame-T. Aman cropping pattern - Islam, MA; Begum, Mst A; Jahangir, MM (International Journal of Agricultural Research, Innovation and Technology, 2014)
The experiment was carried out at FSRD site, Pushpopara, Pabna, during November, 2010 to December, 2011 to observe the comparative performance of integrated plant nutrients management (IPNS) system through the use of organic (cowdung, cowdung slurry) manure and inorganic fertilizer on wheat, sesame and T. Aman crops under wheat-sesame-T. Aman cropping pattern. The experiment was consisted with four treatments viz. T1: Soil test based inorganic fertilizer dose for high yield goal, T2: Cowdung @ 5 t ha-1 + IPNS basis inorganic fertilizer dose for high yield goal, T3: Cowdung slurry @ 5 t ha-1 + IPNS basis inorganic fertilizer dose for high yield goal and T4: Fertilizer dose usually practiced by the farmers. In case of wheat, the highest grain yield (3.80 t ha-1) was obtained from bio-slurry treated plot that means T3 treatment followed by T2 and the lowest (3.31 t ha-1) from T4. Higher seed yield (1.31 t ha-1) of sesame was obtained from T3 that was statistically identical to T2 and T1 and the lower (1.01 t ha-1) from T4. For T. Aman rice, the highest grain yield (4.89 t ha-1) was obtained from T3 which was statistically indistinguishable from T1 where as the lowest grain yield (4.1 t ha-1) was recorded from T4. Considering the whole pattern, it is observed that the highest gross return (271100 Tk ha-1) was obtained from T3 followed by T2 and the lowest (225650 Tk ha-1) from T1 treatment. Total variable cost was recorded as the highest (100368 Tk ha-1) in T2 followed by T3 and the lowest (86775 Tk ha-1) in T4 treatment. The highest marginal value of product (45450 Tk ha-1) was recorded in T3 followed by T2 where as the minimum (28710 Tk ha-1) was found in T1 over the T4 treatment. Marginal variable cost was observed as the highest (13593 Tk ha-1) in T2 treatment followed by T3 and the minimum (8899 Tk ha-1) was recorded in T1 treatment. The highest MBCR (4.15) was recorded from T3 followed by T2 and the minimum (2.31) from T2 treatment. DOI: http://dx.doi.org/10.3329/ijarit.v3i2.17847 Int. J. Agril. Res. Innov. & Tech. 3 (2): 66-71, December, 2013